Mycobacterium tuberculosis: Active disease and latent infection in a renal transplant cohort. Issue 5 (17th April 2019) - Rafiei, Nastaran; Williams, Jackie; Mulley, William R; Trauer, James M; Jenkin, Grant A; Rogers, Benjamin A
ABSTRACT: Aim: Our aim was threefold: first, to determine the incidence of active TB in our cohort, second to investigate the risk factors for active TB and third, to understand current screening practices. The ultimate goal was to use our findings to inform development of local and national guidelines. Methods: The records of all adult patients who underwent renal transplantation at our centre from 2005 to 2014 were retrospectively reviewed to assess current screening practices, the risks for and burden of active TB. Results: A total of 660 individuals underwent renal transplantation during this period, totalling 3647 person years of follow up. Two patients were diagnosed with active TB after renal transplant, resulting in an incidence of 55 per 100 000 person‐years. Of 656 transplant recipients, 102 (15.5%) were born in high TB incidence countries and 89 (13.5%) had an interferon gamma release assay (IGRA) at any point. Individuals born in high TB risk countries had a much higher incidence of active TB (353 per 100 000 person‐years). Ten individuals had positive IGRA tests, of whom two were treated for active TB, two received chemoprophylaxis and six were not treated. Conclusions: In the absence of formal guidelines, IGRA‐based screening for LTBI was infrequently performed. Our data suggest that screening and treatment of renal transplant recipients born in high incidence countries is an important preventive measure. Summary at a Glance: The ever‐increasing global population movement (travel and migration) results in individuals with a high background risk of tuberculosis receiving renal transplants in countries of low TB incidence. This paper confirms the significantly increased risk of active TB among renal transplant recipients from high incidence regions as well as the potential benefit of latent TB screening by interferon gamma release assay.